Activation of G protein-coupled receptors by ketone bodies: Clinical implication of the ketogenic diet in metabolic disorders - Spigoni, Valentina; Cinquegrani, Gloria; Iannozzi, Nicolas Thomas; Frigeri, Giulia; Maggiolo, Giulia; Maggi, Marta; Parello, Vanessa; Dei Cas, Alessandra (Frontiers in Endocrinology, 2022)
Ketogenesis takes place in hepatocyte mitochondria where acetyl-CoA derived from fatty acid catabolism is converted to ketone bodies (KB), namely β-hydroxybutyrate (β-OHB), acetoacetate and acetone. KB represent important alternative energy sources under metabolic stress conditions. Ketogenic diets (KD) are low carbohydrate fat-rich eating strategies which have been widely proposed as valid nutritional interventions in several metabolic disorders due to its substantial efficacy in weight loss achievement. Carbohydrate restriction during KD forces the use of FFA, which are subsequently transformed into KB in hepatocytes to provide energy leading to a significant increase in ketone levels known as “nutritional ketosis”. The recent discovery of KB as ligands of G protein-coupled receptors (GPCR) - cellular transducers implicated in a wide range of body functions - has aroused a great interest in understanding whether some of the clinical effects associated to KD consumption might be mediated by the ketone/GPCR axis. Specifically, anti-inflammatory effects associated to KD regimen are presumably due to GPR109A-mediated inhibition of NLRP3 inflammasome by β-OHB, whilst lipid profile amelioration by KDs could be ascribed to the actions of acetoacetate via GPR43 and of β-OHB via GPR109A on lipolysis. Thus, this review will focus on the effects of KD-induced nutritional ketosis potentially mediated by specific GPCRs in metabolic and endocrinological disorders. To discriminate the effects of ketone bodies per se, independently of weight loss, only studies comparing ketogenic vs isocaloric non-ketogenic diets will be considered as well as short-term tolerability and safety of KDs.